Radiotherapy effect on frequency of Candida spp. and on virulence of C. albicans isolated from the oral cavity of head and neck cancer patients - D. Dambroso; T.I.E. Svidzinski; A.E. Svidzinski; M.M.O. Dalalio; R.A. Moliterno (São Paulo State University (UNESP), 2009)
The aim of this study was to investigate the diversity and prevalence of yeasts, and the virulence of C. albicans found in the oral cavity during the course of ionizing radiation treatment of patients with head and neck tumor (HNTP). Samples from 21 HNTP and 24 healthy controls were isolated and identified. C. albicans isolated from two patients during radiotherapy were analyzed for virulence factors. Radiotherapy induced a higher level of both yeast colonization (81% vs 33%) and non-albicans Candida (NAC) colonization (52.4% vs 4.0%) in HNTP than the control group. Patients were colonized by 5 different NAC species: C. glabrata, C. tropicalis, C. parapsilosis, C. krusei and C. kefir. On the other hand, C. albicans colonization was similar in patients and controls (6/21, 28.6% vs 7/24, 29.2%, respectively). Also, of the 11 patients assessed before and during radiotherapy, 5 (45.5%) were colonized before the start of treatment and another 5 (45.5%) during treatment. All of the latter were colonized by NAC species alone. Moreover, we observed a significant and continuous enhancement of C. albicans virulence as the radiotherapy progressed, in the two patients involved in this test. Thus, it is concluded that radiotherapy is an important predisposing factor for the oral candidiasis, including NAC species. Also, it may facilitate the development of more virulent C. albicans strains.